Rasm Al-Qur’an dan Hal-Hal yang Berkaitan Dengannya - Hakmi Hidayat; Nawwaf Zaky Althaf; Icha Rahma Pangesti; Ananda Amalia Efendi (CV. ITTC INDONESIA, 2024)
Rasm Al-Quran is the science of writing the text of the Al-Quran specifically. Focusing on the spelling of the words used and the shape of the letters, The writing of the Koran during the time of the Prophet Muhammad SAW. Carried out by the Muslim Brotherhood with the aim of uniting Muslims into a kind of mushaf whose reading is the same and so that the verses are arranged in an orderly manner. Therefore, for Muslims troughtout the world, there is no difference in meaning between one mushaf and another, The aim of this discussion is for students to become familiar with and familiar with the Rasm Al-Quran and matters related to it. Apart from that, it is also intended to fulfil the assignments for the Ulumul Qur’am course for the student of the Sharia Economic Law study program at UIN Maulana Malik Ibrahim Malang.